After Mandela the battle for the soul of South Africa - Russell, Alec. (London Windmills, 2009)
'A brisk, lively and vividly written portrait of post-apartheid South Africa' - Peter Godwin, author of "Mukiwa".
Includes bibliographical references index
Keywords: South Africa-History -1994-